STUDI EKSPERIMENTAL GENERATOR ELEKTRIK BERBAHAN BAKAR BIOGAS GUNA MENDUKUNG NET ZERO EMISSION (NZE): Indonesia - I Gede Artha Negara; A.A.N.B Mulawarman; I Gede Santosa; L.P. Ike Midiani (Jurnal Rekayasa Mesin, 2023)
Indonesia is a country that has large, widespread and diverse renewable energy potential that can support energy transition and achieve net zero emission (NZE) target by 2060 or sooner. This paper aimed to investigate characteristics of exhaust emissions and consumption fuel of biogas-fuelled electric generator. The biogas used comes from organic cow dung through an anaerobic fermentation process. About 40% vol. CH4 content observed in biogas. A 420 CC of single cylinder generator was used in this study. Based on the results, it can be seen that biogas exhaust CO emissions are relatively lower than gasoline. CO emissions are directly proportional to the electric load. The lowest CO2 emission was obtained at 4,7 % for biogas with 300 W electric load and 8,4 % for gasoline which is the highest emission. The concentration of hydrocarbons was observed to be 20 ppm for biogas while 64 ppm for gasoline with 300 W electric load. For the fuel consumption, biogas obtained relatively higher results than gasoline for each electric load.